PENDIRIAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH PESANTREN LUHUR SABILUSSALAM - Fatah, Dede Abdul; Waluyo, Bambang; Muchtasib, Ach. Bakhrul Muchtasib; Syafrida, Ida; Hasanah, Nurul (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2021)
Abstract This community service aims to provide knowledge about Islamic cooperatives and to provide assistance and economic empowerment for Sabilussalam Islamic boarding school through the establishment of Islamic Saving–Loan and Financing Cooperatives. Besides, this community service is also one of the Jakarta State Polytechnic (PNJ) real contributions initiated by the Islamic Finance and Banking study program. Islamic Saving–Loan and Financing Cooperatives (KSPPS) is one of the microfinance institutions (LKM) that can serve the needs of the community of micro and small businesses. This institution is able not only to realize the establishment of good systems, methods, techniques and outputs but also to ensure the economic equilibrium within the community. Simultaneously, KSPPS has also become a forum for community synergy and the creation of local wisdom. The local wisdom in question is how to prepare a development infrastructure based on local community participation which has no permanent dependency on aid both from the government and others. The implementation of KSPPS is carried out based on the existing sharia and cooperative rules which do not contradict the sharia law. The power of this spiritual and social values from KSPPS has become a strength for sharia-based cooperatives compared to conventional savings and loan cooperatives. This community service program will be carried out using a method approach as follows; preparation, learning and the establishment of Islamic Saving–Loan and Financing Cooperatives. This community service has greatly assisted Sabilussalam Islamic boarding school in the establishment of Islamic Saving–Loan and Financing Cooperative (KSPPS) which can help the economic independence of the boarding school administrators and the surrounding community.   Keywords –mentoring, counseling, establishment, Islamic saving-loan and financing cooperatives, KSPPS   Abstrak Pengabdian masyarakat ini  bertujuan memberikan wawasan tentang koperasi syariah  bagi  pondok pesantren Sabilussalam, serta memberikan pendampingan dan pemberdayaan ekonomi melalui pendirian Koperasi Simpan Pinjam dan Pembiayaan Syariah. Disisi lain pengabdian masyarakat ini  sebagai kontribusi nyata Politeknik Negeri Jakarta dalam hal ini program studi Keuangan dan Perbankan Syariah. Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) yang merupakan lembaga keuangan mikro (LKM) yang mampu melayani kebutuhan masyarakat pelaku usaha mikro dan kecil. Lembaga ini mampu mewujudkan terbangunnya sistem, metode, teknik dan output yang baik dan perimbangan kekayaan yang tidak hanya berada pada segolongan masyarakat. Secara simultan, KSPPS juga menjadi wadah sinergi masyarakat dan manciptakan kearifan lokal. Kearifan lokal yang dimaksud adalah bagaimana menyiapkan infrastruktur pembangunan berbasis partisipasi masyarakat lokal, yang tidak memiliki ketergantungan permanen pada bantuan, baik dari pemerintah maupun yang lain. Pelaksanaan KSPPS dilakukan dengan bersandar kepada aturan syariah dan aturan koperasi yang ada selama tidak bertentangan dengan hukum syariah. Kekuatan nilai-nilai spiritual dan sosial dari KSPPS ini menjadi kelebihan koperasi berbasis syariah dengan koperasi simpan pinjam konvensional. Dalam menjalankan program pengabdian ini akan dilakukan dengan melakukan pendekatan metode; persiapan, pembelajaran, dan pendirian koperasi simpan pinjam dan pembiayaan syariah. Pengabdian masyarakat ini sangat membantu pondok pesantren Sabilussalam dalam pendirian Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) yang dapat membantu kemandirian ekonomi pengurus pesantren dan masyarakat sekitar.   Kata kunci –pendampingan, penyuluhan, pendirian, koperasi simpan pinjam dan pembiayaan syariah, KSPPS